Diabetes UK evidence‐based nutrition guidelines for the prevention and management of diabetes. Issue 5 (16th April 2018) - Dyson, P. A.; Twenefour, D.; Breen, C.; Duncan, A.; Elvin, E.; Goff, L.; Hill, A.; Kalsi, P.; Marsland, N.; McArdle, P.; Mellor, D.; Oliver, L.; et al.
Abstract: A summary of the latest evidence‐based nutrition guidelines for the prevention and management of diabetes is presented. These guidelines are based on existing recommendations last published in 2011, and were formulated by an expert panel of specialist dietitians after a literature review of recent evidence. Recommendations have been made in terms of foods rather than nutrients wherever possible. Guidelines for education and care delivery, prevention of Type 2 diabetes, glycaemic control for Type 1 and Type 2 diabetes, cardiovascular disease risk management, management of diabetes‐related complications, other considerations including comorbidities, nutrition support, pregnancy and lactation, eating disorders, micronutrients, food supplements, functional foods, commercial diabetic foods and nutritive and non‐nutritive sweeteners are included. The sections on pregnancy and prevention of Type 2 diabetes have been enlarged and the weight management section modified to include considerations of remission of Type 2 diabetes. A section evaluating detailed considerations in ethnic minorities has been included as a new topic. The guidelines were graded using adapted 'GRADE' methodology and, where strong evidence was lacking, grading was not allocated. These 2018 guidelines emphasize a flexible, individualized approach to diabetes management and weight loss and highlight the emerging evidence for remission of Type 2 diabetes. The full guideline document is available atwww.diabetes.org.uk/nutrition-guidelines . What's new?: These updated guidelines, based on recently published studies, provide evidence‐based recommendations for the prevention and management of diabetes. The focus is on food, rather than nutrients, and an individualized, flexible approach to nutritional management is recommended. New guidelines for remission of Type 2 diabetes and considerations for ethnic minorities are included. Guidelines are assessed using adapted 'GRADE' methodology.